Das Vergessen der sechziger Jahre: Entpolitisierte Politik und Hegemonie im neuen China - Hui, Wang (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2008)
After the end of the "Cultural Revolution" an increasing process of depoliticized politics took place in China combined with a state-party rigidification. This process is analyzed and some similarities and parallels to developments in Western countries are shown.